Quality assurance and quality improvement using supportive supervision in a large-scale STI intervention with sex workers, men who have sex with men/transgenders and injecting-drug users in India. (18th February 2010) - Mogasale, Vittal; Wi, Teodora C; Das, Anjana; Kane, Sumit; Singh, Aman Kumar; George, Bitra; Steen, Richard
Abstract : Background: Documentation of the long-term impact of supportive supervision using a monitoring tool in STI intervention with sex workers, men who have sex with men and injection-drug users is limited. The authors report methods and results of continued quality monitoring in a large-scale STI services provided as a part of a broader HIV-prevention package in six Indian states under Avahan, the India AIDS Initiative. Methodology: Guidelines and standards for STI services, and a supportive supervisory tool to monitor the quality were developed for providing technical support to STI component of large-scale HIV-prevention intervention through 372 project-supported STI clinics. The tool contained 80 questions to track the quality of STI services provided on a five-point scoring scale in five performance areas: coverage, quality of clinic and services, referral networks, community involvement and technical support. Results: The tool was applied to different STI clinics during supportive supervision visits conducted once in every 3 months to assess quality, give immediate feedback and develop a quality score. A total of 292 clinics managed by seven lead implementing partners in six Indian states were covered in 15 quarters over 45 months. Overall quality indicators for the five performance areas showed a three- to sevenfold improvement over the period. Conclusion: It was possible to improve quality over the long-term in STI interventions for sex workers, men who have sex with men and injection-drug users using an interactive and comprehensive supportive supervision tool which gives on-the-spot feedback. However, such an effort is time-consuming and resource-intensive, and needs a structured approach.